Trophic Transfer of Microplastics From Copepods to Jellyfish in the Marine Environment - Costa, Elisa; Piazza, Veronica; Lavorano, Silvia; Faimali, Marco; Garaventa, Francesca; Gambardella, Chiara (Frontiers in Environmental Science, 2020)
Microplastics (MPs) can be ingested by marine organisms directly or indirectly through trophic transfer from contaminated prey. In the marine ecosystem, zooplankton are an important link between phytoplankton and higher trophic levels in the marine food web. Among them, copepods and gelatinous species have been recently reported to ingest MPs, but no potential MP transfer has been verified yet. In this study, a simplified two-level trophic chain – formed by nauplii of the Tigriopus fulvus copepod as prey, and the ephyrae stage of Aurelia sp. as predator – was selected to investigate MP trophic transfer. The experimental set-up consisted in feeding ephyrae with nauplii previously exposed to fluorescent 1-5 µm polyethylene MPs and evaluating two ecotoxicological end-points: jellyfish immobility and pulsation frequency. After 24 hours, the jellyfish ingested nauplii contaminated with MPs; however, neither immobility nor behaviour were affected by MP transfer. These findings show that MPs can be transported at different trophic levels, but more research is needed to identify their potential effects on the marine food web.